Energy and Macronutrient Considerations for Young Athletes. Issue 6 (December 2020) - Hannon, Marcus P.; Close, Graeme L.; Morton, James P.
Abstract : ABSTRACT: Young athletes undergo many anatomical and physiological changes during the first 2 decades of life as a result of growth and maturation. Such changes influence a young athlete's nutritional requirements and it is therefore inappropriate to apply nutritional guidelines for adult athletes to this population. Nutritional recommendations for young athletes should not only focus on sporting performance but should also meet the requirements to ensure optimal growth, maturation, and physical development. This review article provides an overview of the nutritional recommendations for young athletes based on the best available literature from a range of sports.